Taliban in Afghanistan, Present and Future: In Search of an Inclusive, Peaceful, Welfare and Sovereign Nation State? - Sahrasad, Herdi; Chaidar, Al; Bayhaki, Imron; Tabrani, Dedy; Mulky, Mohamad Asrori; Ridwan, Muhammad (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The Taliban government is in the world spotlight despite its pledge to aim only at a peaceful, inclusive and sovereign "Islamic government" in Afghanistan. The Taliban said it would not pose a threat to other countries and international community, and they will not repeat the pro-Al Qaeda stance it has in the past. The Taliban are even determined to eradicate terrorism such as ISIS and so on, they would not repeat its violent behavior such as in the past. Of course, the world needs concrete evidence, not just promises, and for that the Taliban needs international help to rebuild Afghanistan. So far, many analysts still view the Taliban as strong and radical Afghan Muslim forces. However, it is also important to remember that the Taliban is not a centralized and unified force so the central government in Kabul must be able to eliminate terrorism and radicalism from any party that threatens the Afghan people and the world community.